Squat Muscle Activation Patterns with Hip Rotations in Subjects with Genu Varum Deformity - Hatefi, Mohamadreza; Babakhani, Farideh; Balouchi, Ramin; Letafatkar, Amir; Wallace, Brian J. (International Journal of Sports Medicine, 2020)
The purpose of this study was to compare muscle activation during the squat with different hip rotations (neutral, 15, 30, and 45° of internal and external hip rotation) in subjects with and without Genu Varum deformity deformity. Surface electromyography were recorded from 32 men with (n=16) and without (n=16) Genu Varum deformity. In the Genu Varum deformity group, the squats with 30, 45 and 15° of internal rotations of the hip showed significantly greater gluteus medius activation as compared to other positions. Moreover, the tensor fascia lata activity increased with greater external rotation of the hip, and significantly more than hip internal rotations (p<0.05). For vastus medialis and vastus lateralis, both hip internal and external rotation showed a significantly greater activation compared to the neutral hip positions (p<0.05). There were significant differences in the gluteus medius:tensor fascia lata activity ratio (p=0.001) and the vastus medialis: vastus lateralis activity ratio (p=0.001) between the different hip positions in the Genu Varum deformity and healthy groups. These results demonstrate that muscle activation patterns varied significantly with the position of different hip rotation in both groups. Those with Genu Varum deformity may use this information to aid in an injury prevention strategy by choosing squat positioning that favorably alters muscle activation patterns.
Keywords: squat; electromyography; genu varum; hip rotation